2019
DOI: 10.1155/2019/7178645
|View full text |Cite
|
Sign up to set email alerts
|

An Institution-Based Assessment of Students’ Hand Washing Behavior

Abstract: Background. Hand hygiene is cost-effective and has been recognized as an effective measure in the control of communicable diseases. The main aim of this study is to evaluate the hand washing knowledge, practices, and skills of students in both private and public institutions of higher learning. Methods. This was an institution-based cross-sectional study that included a mix of 577 university students from different disciplines (49.6% males and 50.4% females) with a mean age of 21.8 ± 3.5 years. Departments wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
16
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 23 publications
3
16
0
3
Order By: Relevance
“…How to wash hands properly, including rubbing This study shows that gender is not significantly related to students' handwashing behavior. These results are consistent with the results of research in the Cameroon, where there is no gender difference in handwashing behavior 47 . However, research reports in North America provide different fact, where female students tend to consistently wash their hands more frequently compared to their male friends and are more effective than the usage of hand sanitizers, and visual prompts 48,49 .…”
Section: Discussionsupporting
confidence: 92%
“…How to wash hands properly, including rubbing This study shows that gender is not significantly related to students' handwashing behavior. These results are consistent with the results of research in the Cameroon, where there is no gender difference in handwashing behavior 47 . However, research reports in North America provide different fact, where female students tend to consistently wash their hands more frequently compared to their male friends and are more effective than the usage of hand sanitizers, and visual prompts 48,49 .…”
Section: Discussionsupporting
confidence: 92%
“…wash their hands for 40-60 seconds). Similar results were seen in the study done by Grace M. Mbouthieu Teumta, et al 19 in which 56.7% of the respondents knew about hand hygiene, but more than half (75.2%) did not follow proper hand-washing techniques. Even in a study done in medical residents in Iran, 20 the residents had moderate knowledge but overall poor attitudes and practices.…”
Section: Discussionsupporting
confidence: 89%
“…We recommend that enhanced educational surveillance measures, particularly in heavily staffed facilities, can improve compliance with handwashing behaviors and thus improve or reduce the risk of disease transmission [26,27]. Surveys showed that medical students (Medicine/Nursing) had a 6.3% higher median hand washing knowledge score when compared with the rest of the students (P = 0.029), in addition, students who wash their hands ≥ 6 times a day had a 18.7% higher median hand washing knowledge score when compared with those who wash their hands ≤2 times a day (P = 0.008), these students also had a higher median hand washing skills score [24]. The results suggested that medical education can improve people's attention to hand hygiene, which suggests healthy education can have a similar effect on health promotion.…”
Section: Discussionmentioning
confidence: 97%
“…Previous studies have shown that the majority of the population is not optimistic about the compliance of hand washing behavior [24]. Unfamiliarity with hand washing methods and forgetting to wash hands are important reasons for the low compliance [24,25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation